Evaluating Grade 5 Teacher Competence Provides Global Education Insights: Mengevaluasi Kompetensi Guru Kelas 5 Memberikan Wawasan Pendidikan Global - Ummah, Siti Roudotul; Wahyuni, Akhtim (Indonesian Journal of Innovation Studies, 2024)
This qualitative study examines the professional competence of Grade 5 teachers at SDN GELAM 1 Candi through interviews, observations, and documentation. The research aims to assess subject mastery, teaching structures, and ongoing professional development. Findings suggest teachers demonstrate competence but have room for improvement in aligning with defined indicators. Emphasizing continuous development, creative content delivery, and technology integration can enhance teaching practices and student learning outcomes. Highlight: Teacher Competence Assessment: Evaluating subject mastery and teaching effectiveness. Ongoing Professional Development: Emphasizing continuous improvement and training. Technology in Teaching: Leveraging tech for enhanced educational practices. Keyword: Professional competence, Grade 5 teachers, Qualitative research, Educational development, Technology integration.